The Fran that time forgot - Benton, Jim. (New York : Simon & Schuster Books for Young Readers, 2005)
When her embarrassing middle name is revealed at school, mad scientist Franny K. Stein experiments with time in order to return to the past and give herself a more dignified name.
Keywords: Science -- Fiction; Time travel -- Fiction; Names, Personal -- Fiction; Humorous stories